Working with people with learning disabilities : theory and practice - Thomas, David, 1962 April 24- (Jessica Kingsley Publishers, 2003)
The authors of this guide bring together the relevant theory for social workers, nurses, teachers and others working with people with learning disabilities. Using jargon-free explanations and case examples they provide the theoretical understanding needed to inform good practice and help to improve the quality of life of the person with a learning disability. They discuss both psychological and practical theories, including: cognitive and behavioural approaches; systems approach; task centred approach; role theory. Emphasising empowerment and inclusion of those with learning disabilities, they.
Keywords: Learning disabilities.; Learning disabled children.; Intellectual disability.; Persons with Intellectual Disabilities -- psychology.; Persons with Intellectual Disabilities -- rehabilitation.; Social Support; Learning Disabilities; Intellectual Disability; Troubles de l'apprentissage.; Enfants en difficulté d'apprentissage.; Déficience intellectuelle.; intellectual disability.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Intellectual disability; Learning disabilities; Learning disabled children